TYPES OF YOUTUBE VIDEO POSTS: Multi-Site Trends Mediated Islamic Networks In Indonesia - Yaqin, Haqqul; Ja’far, Suhermanto (AL-ADYAN, 2025)
This research departs from the phenomenon of the increasing use of YouTube in Indonesia, which ranks as the fourth largest in the world and thus holds a strategic value in disseminating religious messages. The central issue lies in the shift of religious practices into digital spaces, marked by the emergence of new religious communities, the transformation of authority, and the affirmation of identity shaped through Islamic preaching content on YouTube. The purpose of this study is to explain how mediated Islamic networks are formed in cyberspace and how they influence patterns of social interaction and religiosity within society. To address these issues, a qualitative method was employed with a multisite content analysis approach on various Islamic-themed YouTube channels. Data were collected from several popular accounts to map networking patterns, interactions, and audience responses. The findings reveal that the mediatization of religion on YouTube produces at least three significant outcomes: the formation of virtual communities that transcend geographical boundaries, the strengthening of group identity through symbolic and visual narratives, and the shift of religious authority from traditional scholars to digital public figures. In conclusion, YouTube functions not merely as a medium of entertainment but also as a strategic arena for the diffusion of Islamic messages and as a new sphere for the emergence of digital religious practices that influence contemporary understandings and expressions of religiosity.